On the noise immunity and legibility of Lucida fonts - Bowden, Paul R.; Brailsford, David F. (1989)
Modern digital typography often has to contend with output devices such as workstation screens and laser-printers which have a much lower resolution than metal type or phototypesetter machines. In this paper we present results of some legibility investigations in which volunteers were asked to read laser-printed and photocopied material produced in three different typefaces. Two of these faces were not designed with adverse imaging conditions in mind but the third, Lucida, had as one of its design aims that it should be robust and readable at low resolutions. Evidence is presented for Lucida’s enhanced legibility in noisy conditions when compared to the other two faces. However, the difficulties of devising suitable tests and the subjective nature of much of the evidence are also discussed.